2007
DOI: 10.1203/pdr.0b013e31803237f6
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Pressure-Passivity Is Common in the Cerebral Circulation of Sick Premature Infants

Abstract: Cerebral blood flow pressure-passivity results when pressure autoregulation is impaired, or overwhelmed, and is thought to underlie cerebrovascular injury in the premature infant. Earlier bedside observations suggested that transient periods of cerebral pressure-passivity occurred in premature infants. However, these transient events cannot be detected reliably by intermittent static measurements of pressure autoregulation. We therefore used continuous bedside recordings of mean arterial pressure (MAP; from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
336
10
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(365 citation statements)
references
References 27 publications
14
336
10
5
Order By: Relevance
“…However, preterm infants commonly have episodes of impaired autoregulation, primarily due to immaturity of or injury to the cerebral vascular bed (40). Episodes of impaired autoregulation occur in 87 of 90 premature infants <30 wk gestation and may be present 50% of the time during the first 5 d after birth (41). The combination of developmental immaturity and an inability to autoregulate CBF can render the preterm neonatal brain susceptible to injury in response to systemic circulatory disturbances occurring as a result of suboptimal ventilation.…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…However, preterm infants commonly have episodes of impaired autoregulation, primarily due to immaturity of or injury to the cerebral vascular bed (40). Episodes of impaired autoregulation occur in 87 of 90 premature infants <30 wk gestation and may be present 50% of the time during the first 5 d after birth (41). The combination of developmental immaturity and an inability to autoregulate CBF can render the preterm neonatal brain susceptible to injury in response to systemic circulatory disturbances occurring as a result of suboptimal ventilation.…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…The sheep fetus displays cerebral hemodynamics similar to humans and permits repeated physiological measurements in utero in the unanesthetized state. Importantly, similar to the human fetus [77][78][79][80], the fetal sheep displays a very limited range of cerebral autoregulation under normal conditions and a pressure-passive cerebral circulation when subjected to systemic hypoxia and associated hypotension [66,[81][82][83][84]. Moreover, measurements of BP, electroencephalography, blood oxygenation, and other vital variables can be correlated with acute changes in cerebral blood flow and metabolism.…”
Section: Hypoxia-ischemia In Fetal Sheep Generates Pathological Featumentioning
confidence: 99%
“…seizures or IVH) and control preterm infants [28]. Soul et al found impaired cerebrovascular autoregulation in about 20% of the recording time using NIRS in 87 out of 90 very preterm infants during the first 5 days after birth [29]. Other studies also reported on fluctuating autoregulation impairment during the first days after birth [6,[30][31][32][33].…”
Section: Autoregulatory Capacitymentioning
confidence: 99%
“…Clinical factors related to impaired cerebrovascular autoregulation are lower gestational age (GA) [29,34,35], lower birth weight (BW), lower glucose levels [29,34,36], higher clinical risk index for babies (CRIB) score [34], increased infant mortality [34,37], and higher PaCO 2 levels [15,38,39]. Perinatal risk factors such as pregnancy induced hypertension; antepartum hemorrhage and placental infarction are also associated with impaired cerebrovascular autoregulation [29].…”
Section: Clinical Factorsmentioning
confidence: 99%
See 1 more Smart Citation